2016
DOI: 10.1186/s12955-016-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance of the EQ-5D-3L and the EQ-5D-5L in young Portuguese adults

Abstract: BackgroundSome studies have reported a ceiling effect in EQ-5D-3L, especially in healthy and/or young individuals. Recently, two further levels have been included in its measurement model (EQ-5D-5L). The purposes of this study were (1) to assess the properties of the EQ-5D-5L in comparison with the standard EQ-5D-3L in a sample of young adults, (2) to foreground the importance of collecting qualitative data to confirm, validate or refine the EQ-5D questionnaire items and (3) to raise questions pertaining to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 26 publications
(44 reference statements)
11
52
2
2
Order By: Relevance
“…49 Several studies have compared the EQ-5D-3L and the EQ-5D-5L in different countries in both general population samples and specific patient groups, but none of these has examined the two measures in critical care patients. [49][50][51][52][53][54][55][56][57][58][59] The aim of the present study was to compare EQ-5D-3L scores with EQ-5D-5L scores in critical care survivors in the UK. The sample for the present study comprised 359 patients treated at any of the 20 participating UK centres.…”
Section: Background and Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Several studies have compared the EQ-5D-3L and the EQ-5D-5L in different countries in both general population samples and specific patient groups, but none of these has examined the two measures in critical care patients. [49][50][51][52][53][54][55][56][57][58][59] The aim of the present study was to compare EQ-5D-3L scores with EQ-5D-5L scores in critical care survivors in the UK. The sample for the present study comprised 359 patients treated at any of the 20 participating UK centres.…”
Section: Background and Aimsmentioning
confidence: 99%
“…There have been several studies comparing the EQ-5D-5L and EQ-5D-3L in different populations, generally showing that the EQ-5D-5L performs better than the EQ-5D-3L as a result of reduction in ceiling effects [49][50][51][53][54][55][57][58][59] and ability to discriminate between patient characteristics. [52][53][54]56,57 Some studies have shown a high level of agreement between the two measures.…”
Section: Cost-utility Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The values will be situated on a scale that ranges between zero and one, or death and full health. Negative values may be assumed for health states considered worse than death (Drummond et al, 2005;Ferreira, 2010;Ferreira et al, 2013a). The Portuguese version of the EQ-5D was completed in 1998 and published in 2013, by Ferreira and his collaborators (Ferreira et al, 2013a).…”
Section: Preference Based Measures In Healthmentioning
confidence: 99%
“…Negative values may be assumed for health states considered worse than death (Drummond et al, 2005;Ferreira, 2010;Ferreira et al, 2013a). The Portuguese version of the EQ-5D was completed in 1998 and published in 2013, by Ferreira and his collaborators (Ferreira et al, 2013a). The SF-6D was developed from the SF-36 instrument and has six dimensions (physical functioning, role limitation, social functioning, pain, mental health and vitality), each with four to six levels, allowing the generation of 18.000 distinct health states (Brazier et al, 2002).…”
Section: Preference Based Measures In Healthmentioning
confidence: 99%